Інтродукція деревних рослин Кавказу на Волинському Поліссі - Oleshko, V.V.; Doroshenko, O.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The preliminary results of introduction of the Caucasian woody plants on Volyn Polissya are brought on the basis of 20-years researches. The data on their distribution on the territory of Volyn is cited. The features of phenological growth phases and development, high quality of seeds and possibility to obtain planting material of Caucasian woody plants under introduction are studied.